Development of a Novel Assessment Tool and Code Sepsis Checklist for Neonatal Late-Onset Sepsis. (February 2022) - Perkins, Beckett S.; Brandon, Debra H.; Kahn, Doron J.
Abstract : Background: Accurate diagnosis and timely management of neonatal late-onset sepsis (nLOS) have been less well-studied than those of early-onset sepsis. We noticed a delay in nLOS detection and management in our neonatal intensive care unit. Purpose: To develop an assessment tool to aid in the recognition and reporting of nLOS and to standardize the management process once sepsis is recognized. Methods: The Plan-Do-Study-Act (PDSA) improvement model provided the framework for interventions for our antibiotic stewardship program, including the aims of this project. A literature review was performed to evaluate tools and other literature available to guide the evaluation and management of suspected sepsis. A quality improvement project was initiated to develop tools for the detection and management of nLOS. Results: An nLOS assessment tool to help identify neonates at risk for nLOS and a Code Sepsis checklist to standardize the process of evaluation and management of nLOS were developed. The guiding principles of this tool development were empowerment of nurses to initiate the assessment process, clarification of team roles, and removal of barriers to appropriate antibiotic administration. Implications for Practice: Useful and practical tools valued by nursing and the multidisciplinary team may facilitate timely identification and treatment of infants with nLOS. Implications for Research: Future directions include validation of the nLOS assessment tool and the Code Sepsis checklist as well as ensuring the reliability of the tool to improve detection of nLOS and to reduce time to administer antibiotics in cases of nLOS. Abstract : Supplemental Digital Content is Available in the Text.